The Analysis Study of Prevalence, Risk Factor and Management of Thalassemia in Low Income Countries: A Comprehensive Systematic Review - Pambajeng, Cesil Raras; Manalu, Ema Febianti Siskanondang (International Medical Journal Corp. Ltd, 2024)
Background: Thalassemia is a group of inherited blood disorders that impair the body’s ability to produce functional hemoglobin, leading to chronic anemia and other severe health issues. This systematic to evaluate prevalence, risk factors, and management strategies for thalassemia in low-income countries. based on literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Thalassemia prevalence varies significantly across low-income countries, driven by genetic and socioeconomic factors. Effective management requires region-specific strategies, improved access to treatments, and ongoing monitoring. Tailored public health interventions are crucial to reduce the burden and improve patient outcomes.